Judicial Guardianship in Marriage: A Comparative Study of Indonesia’s Shafi'i and Iran’s Ja'fari Schools from a Maqasid al-Shariah Perspective - Thoat Stiawan; Salman Al Farisi; Hisam Sidqi; Agil Laksamana (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
The concept of judicial guardianship in marriage is a significant issue in Islamic family law that highlights the fundamental differences between the Shafi‘i school in Indonesia and the Ja‘fari school in Iran. This distinction is not only juridical but also closely linked to the objectives of marriage (maqasid al-nikah), namely the preservation of religion (hifz al-din), lineage (hifz al-nasl), dignity (hifz al-ird), and family welfare. This study employs a qualitative-juridical approach with normative-comparative analysis. Data were drawn from classical fiqh texts, Indonesian and Iranian marriage regulations, and contemporary literature. The analysis proceeded in three stages: (1) identifying normative texts concerning guardianship and judicial guardianship in the Shafi‘i and Ja‘fari traditions, (2) comparing their conceptual and practical applications, and (3) evaluating their alignment with maqasid al-nikah, particularly in promoting benefits, preventing harm (mafsadah), and ensuring family continuity. The findings show that the Shafi‘i school regards the guardian as a prerequisite for valid marriage, with the judicial guardian acting as a substitute when a lineage guardian is absent or unqualified. By contrast, the Ja‘fari school allows adult women to contract marriage without a guardian, except under specific circumstances. These differences reflect the dynamic nature of Islamic legal thought in responding to social realities, yet both approaches ultimately aim to realize the maqasid al-nikah: legal certainty, protection of dignity, and household stability. The novelty of this research lies in integrating cross-sectarian comparative analysis with the framework of maqasid al-shariah, an approach still rarely applied in studies of Islamic family law, particularly in the Indonesian and Iranian contexts. The implications of this research are twofold: enriching comparative fiqh scholarship as a reference for academic discourse and providing practical insights for the formulation of marriage regulations that remain faithful to shariah while responsive to evolving social dynamics.